Potentials of Innate Immune Memory IIM - Shnawa, Ibrahim M S (British Journal of Healthcare and Medical Research, 2026)
Innate Immune Memory IIM is a twist functional mode of innate immune cells. In the present opinion paper, It is being; conceptualized, immune mechanism explored and potentials explained. IIM is of central and peripheral nature, impart specific long term adaptation for innate immune cells in bone marrow and in peripheral organ tissue microenvironment with marked immune functional plasticity. The IIM stimulants are; infection, microbial macromolecules, vaccination and inflammogen. Mechanisms behind which are; Noncoding RNA, gene circuit regulation, epigenetic reprogramming, circadian rhythm regulation and metabolic shift from oxidative to glycolytic pathways in the innate immune cells. IIM have both protective and pathogenic potentials. The spectrum its functional activities ensembles; Vaccine confer shared immune protection against heterologous infections, an add on immune effect to past infection and past vaccination responses. Though in an unexposed population to second pathogen exposure, it can be synergistic with adaptive immune responses. IIM resilient respiratory and urinary bacterial infections in immune compromised patients. Its role in autoimmune diseases is context dependent. In some AD it promotes pathogenesis and in others its protective. Showcase analysis for human microgial cell, ageing mice and human BCG vaccination models for elucidation of IIM and suggestion for an IIM project for human typhoid. IIM stands as an encouraging scientific base for vaccine production programs and immunotherapeutic targets.